Diagnosing Urinary Tract Infection: Bacterial Count and Gram Identification Using Flow Cytometry - Hayati, Mardiyah; Darmawati, Sri; Santosa, Budi; Lestari, Anak Agung Wiradewi; Limijadi, Edward Kurnia Setiawan; Felim, Jethro (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Urine culture is still the gold standard for Urinary Tract Infection (UTI) diagnostics, but it takes a long time and expensive. The flow cytometry is a more practical, fast, and reliable test for diagnosing UTI. The study was conducted to determine the validity of the bacterial count with UF 5000 flow cytometry compared to urine culture and to evaluate the coherence between Gram identification (BACT-INFO) results and the manual Gram stain.  This was a cross-sectional study aimed to determine the sensitivity, specificity, Positive Predictive Value (PPV), and Negative Predictive Value (NPV) of bacterial count compared to urine culture and to evaluate the coherence between BACT-INFO results with manual Gram stain. Urine from 60 patients diagnosed with suspected UTI was assessed for the ability to diagnose UTI using bacterial count from UF 5000 flow cytometry compared to urine culture and to determine the correlation between BACT-INFO with manual Gram staining results. This study was conducted from January to April 2022. Statistical analysis using the ROC curve showed that the Area Under the Curve (AUC) of the urine bacterial count was 0.856 and by setting a cut-off of 961.8/µL, the sensitivity was 84.0%, specificity 88.9%, PPV 97.7%, NPV 50.0%. The concordance of BACT-INFO compared to manual Gram staining is moderate (obtained from Cohen's Kappa coefficient value 0.3269) with a p-value of 0.0000. The most common bacterial species include Escherichia coli (40.67%), Klebsiella pneumoniae ss pneumoniae (20.33%), Proteus mirabilis (10.17%), Pseudomonas aeruginosa (8.47%), and Acinetobacter baumannii (6.78%). Urine bacterial count based on the flow cytometry method with a cut-off of 961.8/µL has sensitivity and specificity > 80% in diagnosing UTI. There is moderate concordance between BACT-INFO and manual Gram staining. The most common bacteria as the cause of UTI include Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas aeruginosa, and Acinetobacter baumannii.